CORRECTION OF INTERPERSONAL RELATIONSHIPS IN SCHOOL-AGED CHILDREN - Shakhnoza Gapparovna Ibragimova (Galaxy International Interdisciplinary Research Journal, 2022)
In the article, the issue of the study of interpersonal relations of children of junior school age by psychologists, the pedagogical-psychological factors of the issue of the description of correctional work due to the negative impact of the inability to enter into communication on the educational activity and their essence are covered